Microwave-assisted organosolv extraction of coconut shell lignin by Brønsted and Lewis acids catalysts. (10th July 2018) - Avelino, Francisco; Silva, Kássia Teixeira da; de Souza Filho, Men de Sá Moreira; Mazzetto, Selma Elaine; Lomonaco, Diego
Abstract: The fractionation of renewable sources into their components has been extensively explored in order to replace the utilization of the petrochemical compounds. Among those, the obtainment of a high quality lignin for further applications stills a challenge, since its structure is severely affected by the extraction method. The aim of this work was to evaluate the physicochemical and structural effects on coconut shell lignin (CSL) caused by microwave-assisted organosolv delignification (MWAOD) under different acids catalysts. A screening of catalyst concentration and reaction time was employed to optimize the extraction condition for the MWAOD assays. Highest yields were obtained using aqueous solution of acetic acid (90%) combined with 2.0% of AlCl3, H2 SO4 or HCl under 110 °C for 20 min. Extractions using these catalysts were also performed under traditional heating in order to compare the efficacy of microwave irradiation in the yields and chemical structure of lignins. Under the same conditions, MWAOD produced lower molecular weight lignins with higher yields and purities. In terms of monolignol composition, both lignins were quite similar. It can be concluded that microwave-assisted organosolv process is an efficient and eco-friendly procedure for lignin extraction, in a matter of minutes, at high yields and purities, allowing their utilization for further technological applications. Graphical abstract: Highlights: A green and efficient method for lignin extraction was developed. Lignins were extracted under mild conditions and within minutes. Lewis acids can be used as alternative catalysts in the lignin extraction. Hard acids catalysts generated lower molecular weight lignins by microwave heating. Lignins with higher yields, purities and lower molecular masses were obtained.